Fake news and fading views: A vanishing archive of the 1906 Atlanta race massacre. (June 2023) - Jones, Derrick
The absence, erasure, and exile of blackness from the archive breed a silence that has produced grounds for interrogation across numerous disciplines. The official record indexes the authority of the archive to shape what is available for view. Sites of remembrance such as memorials and historical markers are included in the vast material we engage for the sake of history, memory, and meaning. Such a site is the Five Points area of Atlanta, GA, where in 1906, a massacre of black Atlanteans bloodied the landscape and eluded significant remembrance. This article thinks alongside Saidiya Hartman's project of recovery and Christina Sharpe's practice of "wake work" to consider how writing with and against the archive through a blackened consciousness articulate alternative methods of engaging memory and care.